Collaboration for Citizenship Rights: Government and Informal Group in Lemahputro Riverbank, Sidoarjo - Prakasita, Ajeng Widya; Hamdani, Denicha; Adzronnida, Tsabitah Nuril (UIN Sunan Ampel Surabaya, 2025)
The acquisition of basic citizenship rights like legal identity, education, and food security often goes unfulfilled among urban poor communities in Indonesian secondary cities, as they tend to remain invisible to state welfare-delivery systems. Along the Lemahputro riverbank in Sidoarjo, East Java, this exclusion is magnified by residents’ lack of formal documentation, unstable incomes and limited political leverage. This article asks: How do government actors and informal community groups co‑produce solutions to close that citizenship gap? This research conducted a descriptive qualitative case study guided by the concepts of Brokers and Citizenship, Collaborative Governance, and the idea of vernacular citizenship. Data were gathered through participant observation, 17 semi‑structured interviews and document analysis between August and October 2023. Findings reveal a multilevel synergy in which neighborhood and village officials broker legal‑identity access, faith‑based and women’s organizations supply social‑welfare services, and a donor‑initiated hub Griya Sinau functions as an intermediary platform that binds state and community initiatives. This hybrid governance arrangement reduces bureaucratic distance, legitimizes informal actors as policy implementers and expands residents’ repertoires for claiming rights beyond clientelist channels. The study contributes empirically to Indonesian urban‑governance scholarship and conceptually by showing how collaborative governance can be vernacularized through everyday brokerage practices. Policy recommendations include formalizing community brokers as “citizenship facilitators” and deploying mobile civil‑registration units to informal settlements.